Manajemen Strategis Pengelolaan Sampah di Sekolah: Studi Tentang Pembentukan Karakter Peduli Lingkungan SMPN 13 Sijunjung - Putri Eka Gumsi; Suswati Hendriani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to evaluate the environmental care character formation program at SMPN 13 Sijunjung, describe effective strategies, and identify efforts to reduce plastic waste in schools. Using a descriptive qualitative method, the study involved the principal, vice principal, teachers, students, and parents. Data were collected through interviews, observations, and document reviews, analyzed using the Miles and Huberman model. The results show that environmental care characters have been formed through daily habits, supported by strategic school management including teacher training, socialization campaigns, curriculum integration, recycling facilities, collaboration with related parties, and periodic evaluations. This article is expected to increase environmental awareness and actions among junior high school students